Polymorphisms in hOGG1 i XRCC1 DNA repair genes in endometrial cancer - Smolarz, Beata; Romanowicz-Makowska, Hanna; Sobczuk, Anna; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2008)
Aim: In the present work the distribution of genotypes and frequency of alleles of the Ser326Cys hOGG1 gene and Arg399Gln XRCC1 gene polymorphism in subjects with endometrial cancer were investigated. Materials and methods: Blood samples were obtained from 150 women with endometrial cancer and controls (n=129). The polymorphisms were determined by PCR-RFLP. Results: The distribution of genotypes of the Arg399Gln polymorphism of XRCC1 and Ser326Cys polymorphism of hOGG1 in both controls and patients did not differ significantly (p>0.05) from those predicted by the Hardy-Weinberg distribution. There were no significant differences (p>0.05) in genotype distributions or allele frequencies between subgroups assigned to histological stage. Conclusions: The results suggest that the Arg399Gln polymorphism of the XRCC1 gene as well as Ser326Cys polymorphism in hOGG1 may not be linked with appearance and development of endometrial cancer.